2021
DOI: 10.1111/jcpe.13464
|View full text |Cite
|
Sign up to set email alerts
|

Systemic antibiotic therapy as an adjunct to non‐surgical peri‐implantitis treatment: A single‐blind RCT

Abstract: Aim The aim of this single‐blind RCT was to evaluate the adjunctive clinical and microbiological effect of systemic amoxicillin (AMX) plus metronidazole (MTZ) to non‐surgical treatment of peri‐implantitis. Material and methods Patients (N = 62) with peri‐implantitis were randomly assigned to receive full‐mouth mechanical debridement and decontamination and use of chlorhexidine (control group) or combined with antibiotic therapy of AMX/MTZ (test group). Primary outcome was change in bleeding score from baseline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
87
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(93 citation statements)
references
References 40 publications
3
87
1
2
Order By: Relevance
“…Secondary outcomes were also determined in the present research ( Table 3 ). Eleven papers [ 6 , 17 , 22 , 24 , 30 , 49 , 50 , 51 , 52 , 53 , 54 ] reported bone loss. A generalized reduction of approximately 0.75 mm was obtained after 12 months of follow-up ( Table 3 ) when systemic antibiotics were administrated in conjunction with other therapies, such as mechanical debridement, bone graft plus membrane or even titanium granulates.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Secondary outcomes were also determined in the present research ( Table 3 ). Eleven papers [ 6 , 17 , 22 , 24 , 30 , 49 , 50 , 51 , 52 , 53 , 54 ] reported bone loss. A generalized reduction of approximately 0.75 mm was obtained after 12 months of follow-up ( Table 3 ) when systemic antibiotics were administrated in conjunction with other therapies, such as mechanical debridement, bone graft plus membrane or even titanium granulates.…”
Section: Resultsmentioning
confidence: 99%
“…A generalized reduction of approximately 0.75 mm was obtained after 12 months of follow-up ( Table 3 ) when systemic antibiotics were administrated in conjunction with other therapies, such as mechanical debridement, bone graft plus membrane or even titanium granulates. Plaque score was also analyzed in eleven studies [ 1 , 6 , 16 , 22 , 47 , 48 , 50 , 52 , 54 , 56 , 57 ]. Plaque scores in all groups were significantly reduced from baseline to successive follow-up periods when systemic antibiotics were used in combination with complementary therapies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A recently published study (De Waal et al, 2021) investigated the effect of chlorhexidine or amoxicillin/metronidazole as an adjunct to non-surgical therapy in bleeding scores and other clinical and microbiological parameters over a 3-month follow-up period. In contrast to the present study, although they found differences in clinical parameters favouring the use of adjunctive antibiotics, these differences did not reach statistical significance.…”
Section: Discussionmentioning
confidence: 99%